Mobile Arts for Peace (MAP): creating art-based communication structures between young people and policy-makers from local to national levels. Issue 3 (3rd July 2022) - Breed, Ananda; Pells, Kirrily; Elliott, Matthew; Prentki, Tim
ABSTRACT: This article will provide an overview of how the Arts and Humanities Research Council (AHRC) Global Challenges Research Fund (GCRF) project Mobile Arts for Peace (MAP) has attempted to explore the use of interdisciplinary art-based practices for peacebuilding in Rwanda. In particular, we will detail how performance has been used to create a two-way system of communication between young people and policy-makers based on the issues that young people face towards developing an approach to teaching and learning informed by and with young people.